Contribution of drinking patterns to differences in rates of alcohol related problems between three urban populations. Issue 3 (13th February 2004) - Bobak, M; Room, R; Pikhart, H; Kubinova, R; Malyutina, S; Pajak, A; Kurilovitch, S; Topor, R; Nikitin, Y; Marmot, M
Abstract : Objectives: To examine, on empirical data, whether drinking patterns, in addition to overall alcohol consumption, contribute to differences in rates of alcohol related problems between populations. Design: Cross sectional survey. Settings: One Russian, one Polish, and one Czech city. Participants: 1118 men and 1125 women randomly selected from population registers. Main outcome measures: Problem drinking; negative social consequences of drinking; alcohol consumption and drinking pattern. Results: Rates of problem drinking and of negative consequences of drinking were much higher in Russian men (35% and 18%, respectively) than in Czechs (19% and 10%) or Poles (14% and 8%). This contrasts with substantially lower mean annual intake of alcohol reported by Russian men (4.6 litres) than by Czech men (8.5 litres), and with low mean drinking frequency in Russia (67 drinking sessions per year, compared with 179 sessions among Czech men). However, Russians consumed the highest dose of alcohol per drinking session (means 71 g in Russians, 46 g in Czechs, and 45 g in Poles), and had the highest prevalence of binge drinking. In women, the levels of alcohol related problems and of drinking were low in all countries. In ecological and individual level analyses, indicators of binge drinking explained a substantial part of differences in rates of problem drinking and negative consequences of drinking between the three countries. Conclusions: These empirical data confirm high levels of alcohol related problems in Russia despite low volume of drinking. The binge drinking pattern partly explains this paradoxical finding. Overall alcohol consumption does not suffice as an estimate of alcohol related problems at the population level.